Festuca ovina L. As a Monitor Plant Species of Traffic Air Along the Highway in of the City of Warsaw (Poland) - Agata Jędrzejuk; Filip Chyliński; Beata Fornal-Pieniak (Agriculture)
In the urban environment dust particles form a major part of air pollutants and can affect the physiological functions of the plant. Plants proved to be very powerful tools in as-sessing environmental pollution because of their wide distribution. Festuca ovina is a durable plant with specific habitat requirements, but there is no data on physiological response on traffic pollution. The purpose of the study was to measure impact of traffic pollution for Festuca ovina plant to different distance from the source of pollution (highway) basing on physiological markers and microscopical ob-servations. 3 hypoteses were formulated concerning the effect of distance from the source of pollution to the reaction of plants; difference of physiological reaction of leaves and roots to stress conditions; roots as a better indicator of urban pollutions. Current results suggest that Festuca ovina could serve as an effective plant marker for monitoring traffic pollution. The combination of high flavonoid production and reduced free proline concentration in leaves were observed and may suggests the potential tolerance of this plant species to traffic highway pollution. Ammonia content may be a good indicator or ROS accumulation in leaves and roots of plants according to the distance of the pollution source.